The dynamics of student assessment: how academic motivation, student satisfaction, procrastination and academic resilience shape perceptions of authentic assessments - Stephanie Baines; Charlotte Roberts; Pauldy C. J. Otermans (Cogent Education)
Authentic assessments provide an important avenue for preparing students with the comprehensive transferrable skills set they will need in pursuit of their future aspirations. This study explored the relationship between academic motivation, student satisfaction, procrastination, academic resilience and students’ perceptions of authentic assessments. Regression analyses showed that student satisfaction with assessments, and procrastination significantly predict perceptions of authentic assessments. In contrast, students’ academic motivation and academic resilience do not significantly predict perceptions of authentic assessments. In addition, student’s perceptions of authentic assessment predicted preferences for some types of assessment. The study provides insights into the factors that influence students’ perceptions of authentic assessments and suggests areas for improving assessment practices.